Investigation on the Durability of PLA Bionanocomposite Fibers Under Hygrothermal Conditions - Aouat, Tassadit; Kaci, Mustapha; Lopez-Cuesta, José-Marie; Devaux, Eric (Frontiers in Materials, 2019)
Hygrothermal ageing of neat poly(lactic acid) (PLA), PLA/microcrystalline cellulose (MCC) and PLA/cellulose nanowhiskers (CNW) fibers prepared by melt-spinning process was investigated at 95 % relative humidity (RH) and two temperatures, i.e., 45 and 60°C. PLA bionanocomposite fibers were melt compounded at filler content of 1 wt% in the presence of PLA-grafted-maleic anhydride (PLA-g-MA) (7 wt%) used as compatibilizer. The influence of the type of cellulosic filler and the temperature on the hydrolytic degradation kinetics was evaluated through changes in molecular structure and physico-mechanical properties of the samples. The study showed, that all exposed fibers to hygrothermal ageing, were subjected to chain scission mechanism responsible for the decrease in average molecular weight, thermal stability and tensile properties, however, more pronounced after 14 days at 60°C. Furthermore, an increase in crystallinity with a fast crystallization process was noticed for all exposed fibers. The study revealed that the hydrolysis rate increased by 5, 6 and 7 times after 14 days at 60°C compared to 25 days at 45°C for neat PLA, PLA/PLA-g-MA/MCC1 and PLA/PLA-g-MA/CNW1 fibers, respectively. This has been ascribed to the catalytic behavior of the cellulosic fillers which promotes water diffusion into the PLA matrix. Finally, the study concludes to the capacity of PLA fibers to better withdraw to hydrothermal ageing in comparison to PLA/cellulose bionanocomposites. The durability of PLA fibers to hygrothermal degradation is established in the following order: PLA>PLA/PLA-g-MA/MCC1>PLA/PLA-g-MA/CNW1.